Efektivitas Pelaksanaan MBS Dalam Peningkatan Mutu Pembelajaran - Ramli Yusuf (IAIN Ternate, 2016)
School management is one of the affect the quality of education, it can even determine the effectiveness of the curriculum, a variety of learning tools, teaching time and learning process. The concept of school based management was first known in the United States. When questioned school to service the needs of the public. The Performance of educational institutions failing for prepare or produce graduates who are not in accordance with the demands and needs of the workforce, especially in the face of global economic dynamics increasingly competitive. This phenomenon is encouraging people and government to take a strategic and anticipatory to reform school by improving returns management